A study on the application of building information modeling (BIM) in local construction industry / Ahmad Fadli Mohammad - Mohammad, Ahmad Fadli (Faculty of Architecture, Planning and Surveying, 2013)
The construction industry has been facing a paradigm shift to increase productivity, efficiency, infrastructure value, quality and sustainability to reduce lifecycle costs, lead times and duplications by effective collaboration and communication between project team in construction projects. This paradigm shift is becoming more serious and critical with remote construction projects which reveals unique and even more complicated challenging problem in relation to communication and management due to the remoteness of the construction sites. On the other hands. Building Information Modeling (B1M) is offered something that addresses the interdisciplinary inefficiencies in construction projects. Although in many cases the adoption of the B1M has numerous potential benefits, it also raises interesting challenges with regards to how BIM integrates the business process of individual practices. The objectives of the study include identifying the awareness and utilization of BIM system in construction industry; identify the barriers for the implementation of BIM and potential factors in accelerating the BIM adoption in local construction industry. Building Information Modeling (BIM) is a technology that currently were gaining momentum as interoperability issues become more important in relative the quality and its productivity. Although there is bound of benefits that gained from the BIM application, the local construction industry still reluctant to deploy the system in delivery its services.